Self-collected oral, nasal and saliva samples yield sensitivity comparable to professionally collected oro-nasopharyngeal swabs in SARS-CoV-2 diagnosis among symptomatic outpatients. (September 2021) - Gertler, Maximilian; Krause, Eva; van Loon, Welmoed; Krug, Niklas; Kausch, Franka; Rohardt, Chiara; Rössig, Heike; Michel, Janine; Nitsche, Andreas; Mall, Marcus A.; Nikolai, Olga; Hommes, Franziska; et al.
Highlights: Covid-19: Self-swabbing in symptomatic patients - up to 95% sensitivity Covid-19 – Self-swabbing: Sensitivity drops after day 8 of symptoms duration. Self-swabbing is associated with increased ct-values in SARS-CoV-2 RT-PCR. Covid-19 – Self-swabbing: Sensitivity drops with increasing procedural user errors. Self-collection of samples may simplify testing for covid-19 in symptomatic patients. Abstract: Introduction: Containing COVID-19 requires broad-scale testing. However, sample collection requires qualified personnel and protective equipment and may cause transmission. We assessed the sensitivity of SARS-CoV-2-rtPCR applying three self-sampling techniques as compared to professionally collected oro-nasopharyngeal samples (cOP/NP). Methods: From 62 COVID-19 outpatients, we obtained: (i) multi-swab, MS; (ii) saliva sponge combined with nasal vestibula, SN; (iii) gargled water, GW; (iv) professionally collected cOP/NP (standard). We compared ct -values for E-gene and ORF1ab and analysed variables reducing sensitivity of self-collecting procedures. Results: The median ct -values for E-gene and ORF1ab obtained in cOP/NP samples were 20.7 and 20.2, in MS samples 22.6 and 21.8, in SN samples 23.3 and 22.3, and in GW samples 30.3 and 29.8, respectively. MS and SN samples showed sensitivities of 95.2% (95%CI, 86.5-99.0) and GW samples of 88.7% (78.1-95.3). Sensitivity was inversely correlated with ct -values, and became <90% for samples obtained more than 8 days after symptom onset. For MS and SN samples, false negativity was associated with language problems, sampling errors, and symptom duration. Conclusion: Conclusions from this study are limited to the sensitivity of self-sampling in mildly to moderately symptomatic patients. Still, self-collected oral/nasal/saliva samples can facilitate up-scaling of testing in early symptomatic COVID-19 patients if operational errors are minimized.